Saint Thomas Aquinas. - Torrell, Jean-Pierre (Catholic University of America Press, 2023)
"The presentation of the life and work of any great thinker is a formidable task, even for a renowned scholar. This is all the more the case when such a historical figure is a saint and mystic, such as Friar Thomas Aquinas. In this volume, Fr. Jean-Pierre Torrell, OP, masterfully takes up the strenuous task of presenting such a biography, providing readers with a detailed, scholarly, and profound account of the thirteenth-century theologian whose works have not ceased to draw the attention of both friend and foe! In this volume, Fr. Torrell, an internationally renowned expert on St. Thomas, speaks to neophytes and experts alike: for those new to Thomas’s works, he paints an engaging human portrait of Friar Thomas in his historical context; for specialists, he provides a rigorous scholarly account of contemporary research concerning Thomas’s life and work. This new edition of Fr. Torrell’s widely-lauded text involved significant revision, expansion, and bibliographical updates in light of the latest scholarship. The Catholic University of America Press is pleased to present such an eminent specialist’s mature synthesis concerning Friar Thomas Aquinas." --